Shear Strength of Tack Coat on Flexible Pavement and Composite Pavement - Tampanatu P. F. Sompie; Syanne Pangemanan (Journal of the Civil Engineering Forum, 2018)
Tack coat is a thin layer that spread on the surface of existing pavement or concrete pavement. The function of this layer is as an adhesive layer needed to give adhesive power between the existing pavement course and new pavement course or with the concrete pavement, therefore created one strong unity and would bond both, in order to withstand the sheer strength caused by the vehicle load on top of it. Strong adhesiveness of the tack coat course will add sheer strength between the interfaces of the pavement courses. Strong adhesiveness is gained from the asphalt mixed with solvent, therefore created the right viscosity level of the tack coat solution. This research was aimed to measure the sheer strength of tack coat by using modified direct shear asphalt samples. The research method used was by using gauge to measure the sheer strength of tack coat on asphalt sample which was the modified direct shear. While the samples were consisted of 2 types, the asphalt solvent sample as a model of flexible pavement course of AC-WC pavement type with optimum asphalt content of 6.1%, and concrete solvent sample as a model of rigid pavement. These samples were made in briquette form, made with Marshall Mould with 4 inches diameter. The tack coat solvent was made in three solvent variations, which was referring to the standard of the Directorate General of Highways. From this research, it could be concluded that the highest shear strength for flexible pavement was reached on the tack coal solvent mix composition of 30 pph and composite pavement of 15 pph. Tack coat spread rate of 0.25 l/m2 gave highest shear strength on flexible pavement and composition pavement of 0.35 l/m2. Balance was reached on flexible pavement on tack coat variation of 30 pph and 50 pph; while on composite pavement, balance was reached on tack coat solvent variation of 15 pph and 30 pph. This modified direct shear sample could be a method to measure shear strength of tack coat on flexible pavement and composite pavement.